Evaluation of Dietary Glycerin Inclusion During Different Broiler Rearing Phases - Freitas,LW (2017)
ABSTRACT The objective of this study was to evaluate the effect of the dietary addition of different levels of glycerin on the performance, litter moisture, pododermatitis incidence, and carcass and parts yield of broilers. In total, 1,610 broilers were reared in 35 pens with 46 birds each. A completely randomized experimental design, with five treatments with seven replicates was applied. The experimental treatments were: T1: control diet; T2: dietary inclusion of 5% glycerin from 1-42 days of age; T3: dietary inclusion of 10% glycerin from 1-42 days of age; T4: dietary inclusion of 5% glycerin from 7-42 days of age; T5: dietary inclusion of 10% glycerin from 7-42 days of age. The diets containing glycerin fed since the pre-starter period improved broiler weight gain and feed conversion ratio, but did not influence feed intake or livability. At the end of the experiment, the production efficiency index of the broilers fed 10% glycerin during the entire rearing period was significantly reduced compared with the other treatments. Litter moisture in the pens of broilers fed 10% glycerin during the entire rearing period was higher compared to the other treatments since day 21.Diets containing 10% glycerin, both for the entire rearing period (1-42 days) or only after the pre-starter phase (7-42 days), influenced broiler performance and incidence of severe pododermatitis, reducing the production efficiency indexes at 42 days. Glycerin may be added up to 5% in broiler´s diets with no effect on performance, litter moisture and carcass yield, indicating that this co-product of the biodiesel industry can be used as an alternative feedstuff for broilers.